Learning through study circles - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
Responding to the general decline of agricultural extension programmes in the Sahel and elsewhere, Moussa Idi Abdou, an extension officer in Keita, Niger, urges people 'to consider the study circles method which was developed in 1981 by the...